Large-aperture alumina-loaded copper-based catalyst and preparation and application thereof
By using a copper-based catalyst supported by large pore alumina, the problem of insufficient activity and selectivity of ethanol-to-high alcohol catalysts in the prior art is solved, and high ethanol conversion rate and high high alcohol selectivity are achieved, which is particularly suitable for the generation of C6-C10 high carbon alcohols.
Patent Information
- Application Number
- CN202510108637.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing ethanol-to-high alcohol catalysts are difficult to have high ethanol conversion and high high alcohol selectivity, especially higher alcohols with higher carbon count than butanol.
A large pore alumina-supported copper-based catalyst is used, which consists of a large pore alumina support, copper oxide and lanthanum oxide. The pore size and specific surface area of the catalyst are increased by a specific preparation method, thereby improving the reactivity and advanced alcohol selectivity.
Even at lower Cu loading, the copper-based catalyst supported by large pore alumina still maintains high reactivity, significantly improving the ethanol conversion rate and higher alcohol selectivity, especially the selectivity of C6-C10 fatty alcohols.
Smart Images

Figure CN119857488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a macroporous alumina-supported copper-based catalyst, a preparation method thereof and application thereof in the reaction of preparing higher alcohols from ethanol. Background Art
[0002] Biomass is the only renewable organic carbon resource in nature. It can be used to produce high-value-added fuels and chemicals through catalytic conversion. It can play an important role in responding to global climate change, implementing resource substitution strategies, ensuring national energy security and promoting the sustainable development of the chemical industry. Bioethanol, as a renewable clean fuel, has been widely used as a gasoline additive in Europe, the United States, Brazil and China. However, as a fuel, ethanol has low energy density, strong hygroscopicity, and can cause corrosion in the cylinders of automobile engines. Therefore, it is not an ideal gasoline blending component. Compared with ethanol, n-butanol has a higher calorific value, low water solubility, and lower heat of vaporization. It can be mixed with gasoline in a higher ratio and can be used directly without structural modification of existing engines. Therefore, it has the potential to become a new generation of biofuels and be promoted. Similar to butanol, higher alcohols such as hexanol and octanol can also be used as excellent fuel blending components. In particular, they have a higher cetane number and are suitable for use as diesel additives to increase the oxygen content of diesel, thereby significantly reducing particulate matter and nitrogen oxides produced during diesel combustion. In addition to being used as fuel, these higher alcohols are also important industrial solvents and organic synthesis raw materials, and can be used in industries such as coatings, rubber, plastics, cosmetics, and flavors.
[0003] Under relatively mild reaction conditions, ethanol dehydrogenation coupling follows the Guerbet reaction mechanism, and the target product n-butanol undergoes four cascade reaction steps: first, ethanol molecules are dehydrogenated to produce acetaldehyde, then acetaldehyde undergoes aldol condensation to produce 3-hydroxybutyraldehyde, then 3-hydroxybutyraldehyde is dehydrated to produce crotonaldehyde, and finally crotonaldehyde is hydrogenated to produce n-butanol. The products n-butanol and ethanol can further undergo Guerbet reactions to produce alcohols with higher carbon numbers (such as n-hexanol, 2-ethylbutanol, n-octanol, 2-ethylhexanol, etc.). In addition to the main reaction, there are a series of side reactions such as ethanol dehydration to produce ether and ethylene, and ethanol and acetaldehyde react to produce ethyl acetate and 1,1-diethoxyethane, which are not conducive to improving the selectivity of higher alcohols such as n-butanol and n-hexanol.
[0004] The Guerbet mechanism requires four basic reactions in series, involving multiple catalytic active sites such as metal centers and acid-base centers. Metal catalysts supported by porous solid acid-base materials are widely used in the dehydrogenation coupling of ethanol to produce higher alcohols. For example, Benito et al. prepared a Cu-Mg-Al composite oxide catalyst with a Cu loading of 1.0-7.6% for the Guerbet reaction of ethanol. After 6 h of reaction at 488 K and 4 MPa (N2), the catalyst Cu1.0 showed an ethanol conversion rate of 24%, a butanol yield of 13%, and a higher alcohol selectivity of 21.6% [Journal of Cleaner Production, 2019, 209: 1614-1623]. He et al. reported a single-atom Ru catalyst supported by a layered Mg-Al composite oxide and used it for the condensation of ethanol to produce higher alcohols. At 623 K, 0.1 MPa N2, WHSV=3.2 h -1 Under the reaction conditions, the Ru / Mg3Al1-LDO catalyst with a Ru loading of 1.04wt% exhibited an ethanol conversion rate of 29.6% and a higher alcohol selectivity of 82.6% [Applied Catalysis B: Environmental, 2022, 309: 121271-121280]. Although the above catalyst has a high selectivity for higher alcohols, its ethanol conversion rate is low, which increases the separation and recovery cost of ethanol raw materials. In addition, the use of precious metal Ru also makes it difficult to use in practice due to its high price. The 3Cu1CeO2 / AC catalyst reported by Jiang et al. was used in a reactor (reaction conditions: 523 K, 0.1 MPa N2, reaction time 48 h) and a fixed bed (reaction conditions: 523 K, 2 MPaN2, LHSV=4 mL / (h·g cat) showed n-butanol yields of 21.6% and 19.1% respectively [Chemical Communications, 2016, 52(95): 13749-13752]; subsequently, a series of M-CeO2 / AC catalysts loaded with different metals (M=Cu, Fe, Co, Ni and Pd) were prepared, among which Pd-CeO2 / AC catalyst showed the highest n-butanol selectivity (67.6%), while Cu-CeO2 / AC showed the highest ethanol conversion rate (46.2%) [Catalysis Communications, 2017, 100: 15-18]. Although Cu-CeO2 / AC catalyst showed high butanol selectivity, its reaction activity and selectivity for higher alcohols were still not ideal, and the copper loading was high, so the catalyst cost was high; while Pd-CeO2 / AC catalyst had high butanol selectivity, its low catalytic activity and expensive precious metal usage also became its pain points. Patent CN113443964A also reported a Cu-MO x / Al2O3 catalyst (MO x The ethanol conversion rate was 45.6% and the yield of higher alcohol was 26.9% in the reaction of continuous catalytic conversion of ethanol to higher alcohol in a fixed bed. Comparative Examples 1-3 of Patent CN115814805A used particles with a diameter of 0.2 to 5 mm and a specific surface area of 229.2 m 2 / g, average pore size of 10.0 nm, and pore volume of 0.77 mL / g, a granular alumina carrier was used to prepare an alumina-loaded CuO-La2O3 catalyst, which showed 41.8-43.4% ethanol conversion rate and 21.6-27.3% higher alcohol yield in the fixed-bed continuous catalytic conversion of ethanol to higher alcohols.
[0005] In summary, so far, it is difficult for existing ethanol-to-higher alcohols catalysts to achieve both high ethanol conversion rate and high higher alcohol selectivity, especially the selectivity for higher alcohols with higher carbon numbers than butanol is low.
[0006] The present invention prepares a large-pore alumina carrier and uses it as a carrier to prepare a large-pore copper-based catalyst. The large pore size and specific surface area facilitate the diffusion of reactants and reaction intermediates and the conversion of reactions to higher carbon number higher alcohols, so that the catalyst can still maintain high activity even at a lower Cu loading, and is conducive to the generation of higher alcohols with larger molecular weight, so that it has higher selectivity for higher alcohols (especially C6-C10 fatty alcohols). Summary of the invention
[0007] The first technical problem to be solved by the present invention is to provide a copper-based catalyst supported by macroporous alumina for the reaction of ethanol to higher alcohols, so as to improve the ethanol conversion rate and higher alcohol selectivity, thereby improving the higher alcohol yield.
[0008] The second technical problem to be solved by the present invention is to provide a method for preparing a large-pore alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols.
[0009] The third technical problem of the present invention is to provide the application of the macroporous alumina-supported copper-based catalyst in the reaction of ethanol to higher alcohols.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols, wherein the macroporous alumina-supported copper-based catalyst comprises a macroporous alumina carrier and copper oxide and lanthanum oxide supported on the surface thereof, and the content of each component in the macroporous alumina-supported copper-based catalyst is expressed in mass percentage as follows:
[0012] Large pore alumina carrier 79%~98.9%
[0013] Copper oxide 0.1%~6%
[0014] Lanthanum oxide 1%~15%
[0015] The macroporous alumina-supported copper-based catalyst is in granular form with a specific surface area of 250-500 m 2 / g, pore volume is 1.0~2.0 cm 3 / g, and the average pore size is 16~30 nm.
[0016] Preferably, the content of each component in the macroporous alumina-supported copper-based catalyst is expressed as follows in mass percentage:
[0017] Large pore alumina carrier 83%~97.9%
[0018] Copper oxide 0.1%~5%
[0019] Lanthanum oxide 2%~12%.
[0020] As a further preference, the contents of the components in the macroporous alumina-supported copper-based catalyst are expressed in mass percentage as follows:
[0021] Large pore alumina carrier 89%~92%
[0022] Copper oxide 0.5%~3%
[0023] Lanthanum oxide 7%~10%.
[0024] Preferably, the macroporous alumina-supported copper-based catalyst is in granular form with a specific surface area of 250-450 m 2 / g, pore volume is 1.0~2.0 cm 3 / g, and the average pore size is 17~30 nm.
[0025] The macroporous alumina-supported copper-based catalyst of the present invention may contain other components that do not substantially affect its catalytic performance, such as a small amount of impurities introduced by using an alumina carrier, a copper precursor, and a lanthanum precursor.
[0026] In a second aspect, the present invention provides a method for preparing a macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols, comprising the following steps:
[0027] (1) Immerse the prepared macroporous alumina support in a mixed solution of copper and lanthanum precursors, shake and mix, and then let stand for 1 to 48 hours;
[0028] (2) drying the mixture obtained in step (1) so that the copper and lanthanum precursors are evenly loaded onto the inner and outer surfaces of the large-pore alumina support;
[0029] (3) The large-pore alumina carrier loaded with copper and lanthanum precursors obtained by drying in step (2) is placed in a muffle furnace and calcined at 300-800° C. in air or inert gas atmosphere for 0.5-24 h to obtain the large-pore alumina-loaded copper-based catalyst.
[0030] In the above preparation method, the large-pore alumina carrier can be obtained by the following method:
[0031] The aluminum precursor salt solution and alkaline precipitant solution prepared in advance are mixed and stirred at 40-95°C for 20-120 minutes to obtain a milky suspension, and then the suspension is filtered to obtain a filter cake, and the filter cake is fully washed with deionized water. The wet filter cake is prepared into a slurry with a non-ionic surfactant and deionized water, and then added to a reactor for mixing and reacting at 20-120°C for 1-12 hours, and after the reaction is completed, the solid sediment is centrifuged to obtain a solid sediment; the solid sediment is placed in an oven at 40-120°C for 2-8 hours, and then calcined in a muffle furnace at 400-800°C for 2-8 hours to obtain the large-pore alumina carrier.
[0032] In the above-mentioned large-pore alumina preparation method, the aluminum precursor salt is at least one of soluble aluminum salts such as aluminum nitrate, aluminum sulfate, and aluminum chloride, and the mass percentage concentration of the aluminum precursor salt in the aluminum precursor salt solution is 5%~60%; the alkaline precipitant is at least one of alkaline substances such as sodium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water, and the mass percentage concentration of the alkaline precipitant in the alkaline precipitant solution is 5%~75%; the molar ratio of the aluminum precursor and the alkaline precipitant is 1:0.5~1:5; the non-ionic surfactant is at least one of fatty alcohol polyoxyethylene ether and fatty alcohol amide, and the mass percentage concentration of the non-ionic surfactant in the slurry prepared by mixing wet filter cake, non-ionic surfactant and deionized water is 5%~50%.
[0033] In the above-mentioned method for preparing a copper-based catalyst supported by large-pore alumina, the copper precursor can be at least one of soluble copper salts such as copper nitrate, copper chloride, copper acetate, and copper acetylacetonate. The lanthanum precursor can be at least one of lanthanum nitrate and lanthanum acetylacetonate. The solvent for preparing a mixed solution of copper and lanthanum precursors can be at least one of deionized water, methanol, ethanol, isopropanol, acetylacetone, chloroform, tetrahydrofuran and N,N-dimethylformamide. The drying treatment described in step (2) is carried out in a rotary evaporator and an oven, first drying for 1 to 24 hours at 10 to 60°C and 0.005 to 0.1 MPa in a rotary evaporator, and then drying for 1 to 48 hours at 50 to 150°C in an oven.
[0034] In a third aspect, the present invention provides use of the macroporous alumina-supported copper-based catalyst according to the first aspect in the reaction of ethanol to produce higher alcohols.
[0035] The reaction of preparing higher alcohols from ethanol catalyzed by the macroporous alumina-supported copper-based catalyst is continuously carried out in a fixed bed reactor.
[0036] The application of the macroporous alumina-supported copper-based catalyst in the reaction of ethanol to higher alcohols comprises the following steps:
[0037] (1) The macroporous alumina-supported copper-based catalyst is first reduced in situ with ethanol before being used in the ethanol to higher alcohol reaction. The ethanol in situ reduction conditions are as follows: the temperature is 100-325°C (preferably 150-300°C), the carrier gas nitrogen is introduced to control the pressure in the reactor, the pressure is atmospheric pressure-6.0 MPa (preferably atmospheric pressure-5.0 MPa), and the liquid space velocity of ethanol is 0.2-6.0 mL / (g cat ·h) (preferably 0.5~5.0 mL / (g cat·h )), the volume ratio of carrier gas nitrogen and ethanol is 10~1000:1 (preferably 100~800:1), and the reduction time is 0.5~12 h;
[0038] (2) Continuously introducing ethanol and carrier gas nitrogen into a fixed bed reactor to carry out a reaction of producing higher alcohols. The reaction conditions of the reaction of producing higher alcohols from ethanol are as follows: temperature of 150-325° C. (preferably 200-300° C.), pressure of normal pressure to 6.0 MPa (preferably normal pressure to 5.0 MPa), liquid space velocity of ethanol of 0.2-6.0 mL / (g cat ·h) (preferably 0.5~5.0 mL / (g cat h)), the volume ratio of carrier gas nitrogen and ethanol is 10~1000:1 (preferably 100~800:1).
[0039] The higher alcohols described in the present invention include C4-C10 alcohols, namely, aliphatic primary carbon alcohols such as n-butanol, 2-ethylbutanol, n-hexanol, 2-ethylhexanol, n-octanol, 2-ethyloctanol, and n-decanol.
[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0041] (1) When the large-pore alumina-supported copper-based catalyst provided by the present invention is used in the reaction of ethanol to produce higher alcohols, its larger pore size is conducive to the diffusion of raw materials, reaction intermediates, etc. in the pores, especially to the production of higher alcohols with a relatively large molecular weight. Therefore, the catalyst has high reactivity and high selectivity for higher alcohols, especially higher selectivity for C6-C10 fatty alcohols.
[0042] (2) The large-pore alumina carrier provided by the present invention has both large pore size and high specific surface area. The large pore size significantly increases the diffusion rate of raw materials and reaction intermediates in the catalyst pores, and the high surface area makes copper highly dispersed on the catalyst surface, so that even at a lower Cu loading, it still maintains a high catalytic activity, thereby reducing the production cost of the catalyst. At the same time, the catalyst preparation method is simple and reliable, and the reaction conditions are relatively mild, which brings great advantages to the industrial application of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of a fixed-bed reaction device for the dehydrogenation condensation of ethanol to produce higher alcohols: 1-hydrogen cylinder, 2-nitrogen cylinder, 3-raw material bottle, 4-high-pressure constant flow pump, 5-three-way valve, 6-pressure reducing valve, 7-stop valve, 8-mass flow meter, 9-check valve, 10-reaction tube, 11-reaction furnace, 12-condenser, 13 and 14-condensate inlet and outlet, 15-filter, 16-back pressure valve, 17-product collection tank, 18-catalyst bed. DETAILED DESCRIPTION
[0044] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0045] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0046] like Figure 1 As shown, the reaction device used in the present invention includes a nitrogen bottle 2, a raw material bottle 3, a fixed bed reactor, a condenser 12 and a product collection tank 17;
[0047] The fixed bed reactor comprises a reaction tube 10 and a reaction furnace 11. The reaction tube 10 is provided with a catalyst bed 18, a feed inlet is provided at the top, and a discharge port is provided at the bottom. The reaction furnace 11 is used to control the temperature of the reaction tube 10.
[0048] The nitrogen bottle 2 and the raw material bottle 3 are connected to the feed port of the reaction tube 10 respectively, and a pressure reducing valve 6, a stop valve 7, a mass flow meter 8, and a one-way valve 9 are sequentially arranged between the nitrogen bottle 2 and the reaction tube 10; a high-pressure constant-current pump 4 and a three-way valve 5 are sequentially arranged between the raw material bottle 3 and the reaction tube 10;
[0049] The discharge port of the reaction tube 10 is connected to the condenser 12 and the product collecting tank 17 in sequence, and the condenser 12 is provided with a condensed water outlet 13 and an inlet 14; the product collecting tank 17 is provided with an air outlet at the top and a discharge port at the bottom, and the air outlet is connected to the filter 15 and the back pressure valve 16 in sequence for exhaust gas discharge.
[0050] Example 1
[0051] 56.2775 g Al(NO3)3·9H2O was dissolved in 100 ml deionized water, and 37.2685 g NaHCO3 was dissolved in 250 ml deionized water. The two solutions were then mixed at 80°C, stirred for 60 min to form a white suspension, and then filtered to obtain a white filter cake. The filter cake was slurried and washed in 600 ml deionized water for 60 min and then filtered, and the process was repeated 3 times. The obtained filter cake, 11.3110 g fatty alcohol polyoxyethylene ether (AEO-9) and 100 ml deionized water were added to a polytetrafluoroethylene-lined reactor, mixed and reacted at 100°C for 6 h, and the suspension after the reaction was centrifuged in a centrifuge to obtain a solid sediment. The obtained solid sediment was dried in an oven at 80°C for 6 h, and then the obtained solid was calcined in a muffle furnace at 600°C for 2 h to obtain the macroporous alumina carrier.
[0052] Weigh 0.0380 g Cu(NO3)2·3H2O and 0.2385 g La(NO3)3·6H2O and add them to 12 mL deionized water. After they are completely dissolved and mixed evenly, add 1 g of the macroporous alumina carrier and shake and impregnate for 4 h. The above mixture is rotary evaporated on a rotary evaporator at 60°C and 0.01 MPa for 1 h, and the solid matter after rotary evaporation is placed in an oven at 110°C for 4 h, and finally calcined in a muffle furnace at 600°C in an air atmosphere for 3 h to obtain catalyst A. The specific surface area, pore volume and average pore size of catalyst A were determined by N2 physical adsorption method. The specific test method is as follows: first, the sample was vacuum degassed at 200°C for 4 h to remove the adsorbed water and impurity gases, and then N2 physical adsorption was performed at liquid nitrogen temperature (-196°C). Finally, the adsorption-desorption isotherm of the sample was obtained according to the static method; the specific surface area of the sample was calculated from the adsorption isotherm according to the Brunauer Emmett and Teller (BET) equation, and then the pore volume and average pore size were calculated from the desorption isotherm according to the single point method (P / P0=0.99) and the BJH equation. The specific surface area of catalyst A was measured to be 298 m 2 / g, pore volume 1.41 cm 3 / g, and the average pore size is 18.2 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst A are 1.14%, 8.14% and 90.73% respectively.
[0053] Example 2
[0054] The preparation method of catalyst B is the same as that of Example 1, but the amount of Cu(NO3)2·3H2O weighed is 0.0761 g. The specific surface area, pore volume and average pore diameter of catalyst B are determined in the same manner as in Example 1. The specific surface area of catalyst B is 282 m 2 / g, pore volume 1.37 cm 3 / g, and the average pore size is 18.6 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst B are 2.25%, 8.05% and 89.71% respectively.
[0055] Example 3
[0056] The preparation method of catalyst C is the same as that of Example 1, but the amount of Cu(NO3)2·3H2O weighed is 0.0190 g. The specific surface area, pore volume and average pore diameter of catalyst C are determined in the same manner as in Example 1. The specific surface area of catalyst C is 295 m 2 / g, pore volume 1.40 cm 3 / g, and the average pore size is 18.1 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst C are 0.57%, 8.19% and 91.24% respectively.
[0057] Example 4
[0058] The preparation method of catalyst D is the same as that of Example 1, except that the catalyst is calcined in the muffle furnace at a temperature of 500°C. The specific surface area, pore volume and average pore diameter of catalyst D are determined in the same manner as in Example 1. The specific surface area of catalyst D is 301 m 2 / g, pore volume 1.39 cm 3 / g, and the average pore size is 17.9 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst D are 1.13%, 8.15% and 90.72% respectively.
[0059] Example 5
[0060] The preparation method of catalyst E is the same as that of Example 1, except that the catalyst is calcined in the muffle furnace at a temperature of 700°C. The specific surface area, pore volume and average pore diameter of catalyst E are determined in the same manner as in Example 1. The specific surface area of catalyst E is 275 m 2 / g, pore volume 1.34 cm 3 / g, and the average pore size is 19.9 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst E are 1.11%, 8.16% and 90.73% respectively.
[0061] Comparative Example 1
[0062] Catalyst F was prepared in the same manner as in Example 1, except that commercially available alumina (surface area 250.5 m 2 / g, pore volume 0.77 cm 3 / g, average pore size 7.6 nm). The specific surface area of catalyst F was measured to be 235.2 m 2 / g, pore volume 0.74cm 3 / g, and an average pore size of 7.7 nm. The mass percentages of CuO, La2O3 and Al2O3 in Catalyst F are 1.14%, 8.13% and 90.73% respectively. In this comparative example, the determination methods of the specific surface area, pore volume and average pore size of the carrier and Catalyst F are the same as those in Example 1.
[0063] Comparative Example 2
[0064] Catalyst G was prepared in the same manner as in Example 1, except that commercially available alumina (surface area 250.5 m 2 / g, pore volume 0.77 cm 3 / g, average pore size 7.6 nm), and the amount of Cu(NO3)2·3H2O weighed was 0.2281 g. The specific surface area of catalyst G was measured to be 222.5 m 2 / g, pore volume 0.69 cm 3 / g, and an average pore size of 7.5 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst G are 6.45%, 7.70% and 85.85% respectively. In this comparative example, the determination methods of the specific surface area, pore volume and average pore size of the carrier and catalyst G are the same as those in Example 1.
[0065] Comparative Example 3
[0066] Catalyst H was prepared in the same manner as in Comparative Example 2, except that a commercially available alumina carrier (with a specific surface area of 291 m 2 / g, pore volume 0.74 mL / g, average pore diameter 10.1 nm). The specific surface area of catalyst H was measured to be 266.8 m 2 / g, pore volume 0.68 cm 3 / g, and an average pore size of 9.9 nm. The mass percentages of CuO, La2O3 and Al2O3 in catalyst G are 6.50%, 7.72% and 85.78% respectively. In this comparative example, the determination methods of the specific surface area, pore volume and average pore size of the carrier and catalyst H are the same as those in Example 1.
[0067] Example 6
[0068] Reaction device such as Figure 1 As shown, the catalysts A, B, C, D, E, F, G and H prepared in the above examples and comparative examples are respectively loaded into the reaction tube of a fixed bed reactor to carry out a fixed bed continuous catalytic synthesis of higher alcohols. The specific steps are as follows: ethanol and carrier gas nitrogen are continuously introduced into the fixed bed reactor. The reaction conditions are: temperature of 260°C, pressure of 3 MPa, liquid space velocity of ethanol of 2 mL / (g cat h), the volume ratio of carrier gas nitrogen and ethanol was 250:1. When the reaction reached stability, the liquid product was taken for detection. The liquid product was analyzed using a gas chromatograph equipped with a flame ionization detector (FID) and an HP-5 column (30 m, 0.25 mm). 2-Ethylhexanol was used as the internal standard for the quantification of the liquid product.
[0069] The calculation method of ethanol conversion rate, higher alcohol selectivity and yield is as follows:
[0070]
[0071]
[0072]
[0073] The carbon mole number is the total mole number of carbon atoms contained in the product or raw material ethanol.
[0074] The reaction results are shown in Table 1.
[0075] Table 1 Reaction performance of different catalysts in the continuous catalytic synthesis of higher alcohols by ethanol fixed bed
[0076]
[0077] As shown in Table 1, compared with the Cu-based catalyst prepared with a commercial alumina carrier having a smaller pore size, the ethanol conversion rate and the selectivity of higher alcohols on the Cu-based catalyst supported by large-pore alumina are significantly improved, especially the selectivity of C6-C10 fatty alcohols with higher added value is significantly increased. Its larger pore size and specific surface area not only increase the diffusion rate of raw ethanol, reaction intermediates, etc. in its pores, but also facilitate the formation of higher alcohols with larger molecular weight, thereby significantly improving the activity of the catalyst (even at a lower Cu loading, it still maintains a higher ethanol conversion rate), and at the same time significantly improves the selectivity of higher alcohols, especially the selectivity of C6-C10 higher alcohols with higher added value.
Claims
1. A macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols, characterized in that: The large-pore alumina-supported copper-based catalyst comprises a large-pore alumina carrier and copper oxide and lanthanum oxide supported on the surface thereof. The content of each component in the large-pore alumina-supported copper-based catalyst is expressed in mass percentage as follows: Large pore alumina carrier 79%~98.9% Copper oxide 0.1%~6% Lanthanum oxide 1%~15% The macroporous alumina-supported copper-based catalyst is in granular form with a specific surface area of 250-500 m 2 / g, pore volume is 1.0~2.0 cm 3 / g, and the average pore size is 16~30 nm.
2. The macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols according to claim 1, characterized in that: The content of each component in the macroporous alumina-supported copper-based catalyst is expressed as follows in mass percentage: Large pore alumina carrier 83%~97.9% Copper oxide 0.1%~5% Lanthanum oxide 2%~12%.
3. The macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols according to claim 2, characterized in that: The content of each component in the macroporous alumina-supported copper-based catalyst is expressed as follows in mass percentage: Large pore alumina carrier 89%~92% Copper oxide 0.5%~3% Lanthanum oxide 7%~10%.
4. The macroporous alumina-supported copper-based catalyst for the reaction of ethanol to higher alcohols according to any one of claims 1 to 3, characterized in that: The macroporous alumina-supported copper-based catalyst is in granular form with a specific surface area of 250-450 m 2 / g, pore volume is 1.0~2.0 cm 3 / g, and the average pore size is 17~30 nm.
5. A method for preparing a macroporous alumina-supported copper-based catalyst for ethanol to higher alcohols reaction according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Immerse the macroporous alumina support in a mixed solution of copper and lanthanum precursors, shake and mix, and then let it stand for 1 to 48 hours; (2) drying the mixture obtained in step (1) so that the copper and lanthanum precursors are evenly loaded onto the inner and outer surfaces of the large-pore alumina support; (3) The large-pore alumina carrier loaded with copper and lanthanum precursors obtained by drying in step (2) is placed in a muffle furnace and calcined at 300-800° C. in air or inert gas atmosphere for 0.5-24 h to obtain the large-pore alumina-loaded copper-based catalyst.
6. The preparation method according to claim 5, characterized in that: The macroporous alumina carrier is obtained by the following method: The aluminum precursor salt solution and the alkaline precipitant solution prepared in advance are mixed and stirred at 40-95°C for 20-120 minutes to obtain a milky white suspension, and then the suspension is filtered to obtain a filter cake, and the filter cake is fully washed with deionized water; the wet filter cake is prepared into a slurry with a non-ionic surfactant and deionized water, and then added into a reactor for mixing and reacting at 20-120°C for 1-12 hours, and after the reaction is completed, the solid sediment is obtained by centrifugation; the solid sediment is placed in an oven at 40-120°C for 2-8 hours, and then calcined in a muffle furnace at 400-800°C for 2-8 hours to obtain the large-pore alumina carrier.
7. Use of the macroporous alumina-supported copper-based catalyst as claimed in any one of claims 1 to 4 in the reaction of ethanol to produce higher alcohols.
8. The use according to claim 7, characterized in that: The reaction of preparing higher alcohols from ethanol is carried out continuously in a fixed bed reactor.
9. The use according to claim 8, characterized in that: The application comprises the following steps: (1) The copper-based catalyst supported by the macroporous alumina is first reduced in situ with ethanol before being used in the ethanol to higher alcohol reaction. The ethanol in situ reduction conditions are as follows: the temperature is 100-325°C, the carrier gas nitrogen is introduced to control the pressure in the reactor, the pressure is normal pressure-6.0 MPa, and the liquid space velocity of ethanol is 0.2-6.0 mL / (g cat ·h), the volume ratio of carrier gas nitrogen and ethanol is 10~1000:1, and the reduction time is 0.5~12 h; (2) Continuously introducing ethanol and carrier gas nitrogen into a fixed bed reactor to produce higher alcohols, wherein the reaction conditions of the ethanol to higher alcohols reaction are: temperature of 150-325°C, pressure of normal pressure-6.0 MPa, liquid space velocity of ethanol of 0.2-6.0 mL / (g cat h), the volume ratio of carrier gas nitrogen and ethanol is 10~1000:
1.
10. The use according to claim 9, characterized in that: The application comprises the following steps: (1) The macroporous alumina-supported copper-based catalyst is first reduced in situ with ethanol before being used in the ethanol to higher alcohol reaction. The ethanol in situ reduction conditions are as follows: the temperature is 150-300°C, the carrier gas nitrogen is introduced to control the pressure in the reactor, the pressure is normal pressure-5.0 MPa, and the liquid space velocity of ethanol is 0.5-5.0 mL / (g cat ·h), the volume ratio of carrier gas nitrogen and ethanol is 100~800:1, and the reduction time is 0.5~12 h; (2) Continuously introducing ethanol and carrier gas nitrogen into a fixed bed reactor to produce higher alcohols, wherein the reaction conditions of the ethanol to higher alcohol reaction are: temperature of 200-300°C, pressure of normal pressure-5.0 MPa, liquid space velocity of ethanol of 0.5-5.0 mL / (g cat ·h), the volume ratio of carrier gas nitrogen and ethanol is 100~800:1.
Citation Information
Patent Citations
Compound higher alcohol catalyst, preparation method and application
CN108043403A
Alumina supported copper-rare earth metal oxide catalyst as well as preparation method and application thereof
CN113332989A
Metal oxide promoted copper-based catalyst with hydrogen transfer hydrogenation activity and preparation and application thereof
CN115814805A
Supported composite metal-oxide catalyst, preparation thereof and application of supported composite metal-oxide catalyst in direct synthesis of high-carbon isoolefin from methanol and ethanol
CN117123220A
Copper-based catalyst as well as preparation method and application thereof
CN118002187A
Cited By
Production device and method for continuously rectifying and separating ethanol, n-butyl alcohol and higher alcohol
CN121003828A
An apparatus and method for continuous rectification separation of ethanol, n-butanol and higher alcohols
CN121003828B
Continuous rectification and separation device for mixed liquor after reaction for preparing higher alcohol through catalytic conversion of ethanol and operation method of continuous rectification and separation device
CN121513763A